Electronic forms of entertainment in the context of physical activity and addiction risk – a knowledge review - Grajek, Mateusz; Rozmiarek, Mateusz; Sobczyk, Karolina; Sas-Nowosielski, Krzysztof (Journal of Education, Health and Sport, 2022)
A new way of spending leisure time browsing the Internet, using social networking sites, and playing games has created a new health problem: cell phone addiction. So-called phonoholism or netholism is most thriving among young people, who prioritize entertainment in the real world, which most often necessitates physical activity, over entertainment in the virtual world, which requires a more static approach. However, some companies have gone against the traditional use of phone games by creating multimedia city games that require a dynamic-movement approach. The aim of this review is to gather current theoretical knowledge about electronic forms of entertainment in the context of their influence on users' physical activity, creation of health potential and formation of risk of addiction to such forms of entertainment.